Analysis of the Characteristics of Cow Dung Waste Biopellets with Cassava Peel Starch Adhesive as an Alternative Fuel - Kusuma, Indra; Sulistiawan, Agus; Yuwita, Pelangi Eka (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2025)
This study aims to analyze the characteristics of biopellets made from the raw material of dried cow dung waste with cassava peel starch as an adhesive. The research method was carried out experimentally through several stages: raw material preparation, drying of cow dung under sunlight for 14 days, mixing with variations of cassava peel starch adhesive of 10%, 30%, and 50%, molding using a hydraulic press with pressures of 50, 60, and 70 kg, and testing the characteristics of the biopellets. The parameters tested included calorific value, moisture content, combustion rate, and ash content. The results showed that variations in adhesive levels and molding pressure affected the quality of the biopellets. The calorific value obtained ranged from 2,795.4 to 3,595.9 cal/g, moisture content 9.5–12.5%, combustion rate 0.74–1.71 g/min, and ash content 0.90–1.20%. In conclusion, biopellets from cow dung with the addition of cassava peel starch adhesive have characteristics that are feasible to be developed as an environmentally friendly alternative fuel.